Reconstruction accuracy for visual calibration method - Elipot, M.; Houel, N.; Hellard, P.; Dietrich, G. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Motion analysis is a common technique in biomechanics and sport studies. Since Abdel-Aziz and Karara (1971), the direct linear transformation (DLT) is the most widely used method to analyse human movements. More recently, Drenk et al. (1999) proposed a modified DLT method, called DLT double-plane method (DLT DP), which involves two parallel control planes (rather than a whole 3D structure). With these two calibration methods, a set of coefficients is calculated. This set summarise indirectly the internal and external parameters of the camera. Kwon et al. (2002) and Elipot et al. (2008) have respectively shown that, in aerial and underwater conditions, the DLT DP method can reduce the reconstruction error.